Chemical treatment of maize stover with urea - Muñoz F.; Joy M.; Andueza J.D.; Alibés X. (Exploitation of Mediterranean roughage and by-products, 1998)
The purpose of this work is to describe the use of the urea treatment to improve the nutritive value of maize stover and the main factors that influence the effectiveness of the treatment: dose, moisture, temperature, and source of ureases. Treatments with urea improve the nutritive value of ligno-cellulosic residues, but the response of the maize stover to the treatment is very variable according to literature. Animal response to urea treatments is similar to that observed with anhydrous ammonia treatment. This response is optimum with moderately yielding animals. Animals need supplementation in those periods of high requirements.